A General Strategy to Boost Electrocatalytic Nitrogen Reduction on Perovskite Oxides via the Oxygen Vacancies Derived from A‐Site Deficiency. Issue 11 (29th January 2021) - Chu, Kaibin; Liu, Fuzhu; Zhu, Jiawei; Fu, Hui; Zhu, Haiyan; Zhu, Yinlong; Zhang, Yu; Lai, Feili; Liu, Tianxi
Abstract: The electrocatalytic N2 reduction reaction (NRR) under ambient conditions is an attractive strategy for green synthesis of NH3 . Due to the ultra‐stable NN covalent triple bond, it is very challenging to develop highly selective and efficient electrocatalysts toward NRR. Here a general strategy to enhance the NRR activity through modulating A‐site‐deficiency‐induced oxygen vacancies of perovskite oxides is reported. One successful example is La x FeO3− δ (L x F, x  = 1, 0.95, and 0.9) perovskite oxides with tunable oxygen vacancies that are directly proportional to the La‐site deficiencies. As compared to the pristine LF, the L0.95 F and L0.9 F exhibit significantly improved NRR activities, which are positively correlated with the La‐site deficiency and the amount of oxygen vacancies. Among them, the L0.9 F delivers the best activity, with an NH3 yield rate of 22.1 µg·h −1 ·mg −1 cat. at −0.5 V and a Faradaic efficiency of 25.6% at −0.3 V, which are 2.2 and 1.6 times those of the pristine LF, respectively. Both experimental characterizations and theoretical calculations suggest that the enhanced NRR activity can be mainly attributed to the favorable merits produced by the oxygen vacancies: the promoted adsorption/activation of reaction species, and thus optimized reaction pathways. Application of this strategy to other perovskite oxides generates similarly successful results. Abstract : Tuning the oxygen vacancies induced by A‐site deficiency has been demonstrated as a general strategy for enhancing the electrocatalytic nitrogen reduction reaction (NRR) activity of perovskite oxides. Both the experimental characterizations and theoretical calculations suggest that the enhanced NRR activity can be mainly attributed to the favorable merits produced by the oxygen vacancies: the promoted adsorption/activation of reaction species and thus the optimized reaction pathways.